Assessment of Parental Attitude towards the Teaching of Sex Education in Secondary Schools in Kaduna State - Musa, Paul Hannatu; Enyikwola, Rebecca Onyebi (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
The purpose of the study was to assess Parental Attitude towards the Teaching of Sex Education in Secondary Schools in Kaduna State. To achieve the purpose, ex-post facto research design was used. The instrument used for the study was questionnaire which was divided into six (6) sections. Section (A) contains the demographic characteristic of the respondents, B- parental attitude towards the teaching of sex education in secondary schools, C- Attitude of parents in urban and rural areas towards the teaching of sex education. D- Attitude of parents of various marital statuses. E- Differences between male and female attitude towards the teaching of sex education in secondary schools. The questionnaire was administered to a total of 460 parents, but 362 were filled and return 78.7% responses rate. Data was statistically analysed. The result of the finding shows that, there is no significant difference between parental attitude towards the teaching of sex education, majority of the respondents supported the teaching sex education in secondary schools, parents attitude changes based on their marital status, parent in urban and rural areas do not have similar attitude towards the teaching of sex education. It was therefore recommended that (1) Teaching of sex education should be encourage in all secondary schools (2) Parents in urban and rural areas should be educated to develop positive attitude towards the teaching as well as educating the children at home on the subject matter. Keywords: Parental Attitude Teaching Sex Education.